Reviving Local Wisdom: Teaching Social Values through Lampung in Indonesian Education - Ananda, Lola; Nurulanningsih, Nurulanningsih; Asante, Joyce Nsiah; Shah, Nabia Manzoor (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study explores the integration of social values in the Lampung folklore Legenda Lubuk Sendawali by K. Usman, and its potential in character education. This study uses a naturalistic qualitative approach with data analysis techniques using content analysis. Data were collected through documentation and analyzed in depth. The results showed 53 findings of social values categorized into compassion, responsibility, and harmony in life. The values of compassion include devotion (2 findings), helping each other (15 findings), loyalty (9 findings), and caring (15 findings). The values of responsibility include a sense of belonging (3 findings), discipline (2 findings), and empathy (4 findings). The values of harmony in life include justice (1 finding) and cooperation (2 findings), while the values of democracy and tolerance were not found. The novelty of this study lies in the in-depth study of social values in Lampung folklore, which have rarely been studied in previous studies. This study enriches the understanding of local cultural heritage and provides new insights into how traditional narratives can support character education. The findings of this study have significant implications for character education, especially in implementing the Merdeka Curriculum. Educators can create more engaging, context-based learning that promotes social, moral, and cultural values by integrating folktales into language learning.